Pembuatan Peta Administrasi Gampong Luthu Lamweu Kecamatan Sukamakmur, Kabupaten Aceh Besar - Faisal, Ruhdi; Mutiawati, Cut; Suryani, Fitrika Mita; Saleh, Sofyan M.; Taufiq, Luthfi Chaliqi (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
Maps are a tool for communicating between map makers and map users, so that maps are required to be able to present the functions and information of the objects depicted optimally. The aim of the service is to create an administrative map. The regulations used in making this map are regulations issued by the Head of the Geopatial Information Agency (PerKaBIG) Number 3 of 2016 concerning Technical Specifications for Presenting Village Maps. Making this map uses tools in the form of GIS (Geographic Information System) software. This data collection was carried out by mapping hamlet boundaries using Google Earth Pro software, then the results were extracted into the GIS application, then adjustments were made to the map data into map form and reproducing or printing the map in map form. The map that will be created is an administrative map of the division of hamlets into villages or also called Gampong in Acehnese. This map was made in Gampong Luthu Lamweu, Sukamakmur District, Aceh Besar Regency which has three hamlets, namely Amplam Batee Hamlet, Lamweu Hamlet and Lam Ara Hamlet. Administratively, Luthu Lamweu Gampong is bordered to the north by Reuhat Tuha Gampong, to the south by Gampong Aneuk Glee Mountain/Bukit Barisan, to the east by Gampong Baet Mesjid and to the west by Luthu Dayah Krueng Gampong.